2023
DOI: 10.5194/bg-20-383-2023
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling dryland carbon and water fluxes with artificial neural networks of optical, thermal, and microwave satellite remote sensing

Abstract: Abstract. Earth's drylands are home to more than two billion people, provide key ecosystem services, and exert a large influence on the trends and variability in Earth's carbon cycle. However, modeling dryland carbon and water fluxes with remote sensing suffers from unique challenges not typically encountered in mesic systems, particularly in capturing soil moisture stress. Here, we develop and evaluate an approach for the joint modeling of dryland gross primary production (GPP), net ecosystem exchange (NEE), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 112 publications
1
7
0
Order By: Relevance
“…2 cannot be quantitatively compared to previous cross validation results in FLUXCOM as the training data are not the same. However, qualitatively the accuracy gradient among fluxes as well as along scales of variability corresponded to patterns identified in FLUXCOM and in comparable empirical modeling activities (Jung et al, 2011;Tramontana et al, 2016;Virkkala et al, 2021;Dannenberg et al, 2023).…”
Section: Cross-validation and Data Spacesupporting
confidence: 57%
See 1 more Smart Citation
“…2 cannot be quantitatively compared to previous cross validation results in FLUXCOM as the training data are not the same. However, qualitatively the accuracy gradient among fluxes as well as along scales of variability corresponded to patterns identified in FLUXCOM and in comparable empirical modeling activities (Jung et al, 2011;Tramontana et al, 2016;Virkkala et al, 2021;Dannenberg et al, 2023).…”
Section: Cross-validation and Data Spacesupporting
confidence: 57%
“…By today, the empirical up-scaling concept has been implemented for a series of regional and global scale applications, each of them adopting disparate and individual methodological choices (e.g. Ichii et al, 2017;Yao et al, 2018;Joiner and Yoshida, 2020;Virkkala et al, 2021;Dannenberg et al, 2023;Burton et al, 2023). These potentially important choices relate to data treatment (quality control, gap-filling, processing pathways), ingestion (sampling, as well as matching EC and spaceborn observations), and methodological configurations (machine learning methods and their training configuration, choice of predictor variables, resolution).…”
Section: Introductionmentioning
confidence: 99%
“…500m). Alternatively, models could be trained at a high resolution and applied to the coarse resolution to reduce computation and storage requirements (Dannenberg et al, 2023). However, this approach does not address inherent scaling errors in coarse-resolution satellite images (Yan et al, 2016a;Dong et al, 2023).…”
Section: Input Predictors and Controlling Factorsmentioning
confidence: 99%
“…Furthermore, information about resource limitations and stress factors can be crucial for certain biomes and/or under specific conditions (Stocker et al, 2018). For example, Dannenberg et al (2023) found that incorporating LST from MODIS and soil moisture from the SMAP satellite datasets improved the machine learning estimation accuracy of GPP in drylands from R 2 ~ 0.4 to 0.7 for dryland sites in North America. CEDAR-GPP integrated multi-source satellite observations (optical, thermal, microwave) as well as climate variables to obtain comprehensive information about GPP dynamics.…”
Section: Input Predictors and Controlling Factorsmentioning
confidence: 99%
See 1 more Smart Citation